(untitled) (Journal of Advanced Research in Social Sciences, 2019)
The aeronautical profession of fighter pilots on supersonic aircraft is strongly connected to the motivation, performance and excellence achievement-striving. The supersonic pilot represents the highest and most desirable position in the air force. Research showed that their selection is made by choosing the potential elite candidates after testing the physical, mental abilities and personality traits specific to this profession. The present research examined the personality trait of conscientiousness with achievement-striving facet in fighter pilots on supersonic aircrafts, by using the “IPIP NEO” (International Personality Item Pool NEO) based on Big Five by comparison of two groups, one of fighter pilots on supersonic aircraft and one of non-pilots. The results indicated that fighter pilots on supersonic aircraft have higher level of excellence achievement striving in their performance, they tend to be more competitive to become the best and the desire for victory is needed in their highly risky air missions.